PERANCANGAN VISUAL IDENTITY OPTIK ANTOKAN LUBUK BASUNG - Muhammad Arif; m.nasrul kamal; riri trinanda (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
Optik Antokan Lubuk Basung is a business that operates in the field of eyewear services located at Jalan VII of the Padang Baru Impres Market, Lubuk Basung. Optik Antokan was founded in 2010 and is managed by Aan Goechi as the founder and leader until now. Optical Antokan requires a visual identity that includes logos, colors and fonts, as well as the rules in its application, in accordance with the references specified by the designer in the manual as the main media, in order to establish an affirmed identity, improve business image, according to the distinctions and uniqueness provided for Antokan Optics.Optical Identity Visual Design Method used by the author uses the Glass Box method. This design method starts from data collection, interview and observation. Related problems that occur can be known, as well as the discussion of problems that are analyzed using the SWOT theory (strengths, weaknesses, opportunities, threats). The main media used in this visual identity is the Manual Book / BrandGuidelines. In addition to the main media, this visual identity is complemented by supporting media such as stationery sets, paperbags, x-banners, stickers, posters, glasses boxes, lens cleaners, and t-shirts which support to support the use of the main media.Keyword : Visual Identity, Optik Antokan, Media.